Large-deformation consolidation analysis of foundations based on the elliptical cylinder equivalent drainage plate theory - Aiwu Yang; Tianli Liu; Shaopeng Yang (PLoS ONE, 2026)
Building upon the elliptical cylinder equivalence model, this study integrates the nonlinear variations in soil compressibility and permeability, together with the attenuation behavior of vacuum pressure, to develop large-deformation consolidation models that account for both vacuum loss and the effective influence zone at the base of drainage plates. Corresponding numerical solutions are derived. The results demonstrate that the model incorporating the bottom influence zone exhibits close agreement with experimental data from capped drainage plate tests, validating the rationality and applicability of the proposed consolidation framework and its numerical implementation. In contrast, the model considering only vacuum loss yields greater deviations relative to the experimental results. This finding indicates that neglecting the bottom influence zone of the drainage plate leads to an underestimation of total settlement, thereby misrepresenting the long-term consolidation behavior of ultra-soft soil foundations.